Pengaruh Penggunaan Flipbook pada Materi Tekanan Zat terhadap Kemandirian dan Hasil Belajar Siswa SMP - Lestari, Septiana Indah; Indrawati, Indrawati; Budiarso, Aris Singgih (Program Studi Pendidikan IPA, FKIP Universitas Pancasakti (UPS) Tegal, 2022)
The aims of this study were to (1) examine the effect of using flipbooks on substance stress material on the learning independence of junior high school students and (2) examine the effect of using flipbooks on substance stress material on junior high school students' learning outcomes. The type of research used is experimental and the design used is quasi-experimental with a non-equivalent control group design. The place of research is SMP Negeri 1 Glenmore in the even semester of the 2020/2021 academic year. Data collection techniques used, namely tests, observation of student skills, questionnaires, and documentation. Techniques to analyze the data using the t-test. Results of Sig. (2-tailed) on the t-test on learning independence is smaller than 0.05, which is 0.000. Learning outcomes in this study consisted of the realm of knowledge and skills. Learning outcomes in the realm of knowledge and skills were obtained by Sig. (2-tailed) on the t-test is less than 0.05 (Sig. < 0.05) which is 0.000.